High sensitivity fiber optic temperature sensor composed of two parallel FPI and enhanced harmonic Vernier effect - Huiling Huang; Chao Jiang; Xiaoshan Guo; Simei Sun; Tingshui Cao; Long Zhang; Tianqi Yan (Scientific Reports)
Abstract A high-sensitivity fiber optic temperature sensor based on the enhanced harmonic Vernier effect (HVE) is proposed, which consists of two Fabry–Perot interferometers (FPI) that are sensitive to temperature and connected in parallel. FPI1 is a polydimethylsiloxane (PDMS) cavity formed by filling a ceramic ferrule with PDMS, and FPI2 is an air-cavity formed by inserting a single-mode fiber into a ceramic ferrule coated with PDMS film on the end face. FPI1 and FPI2 have opposite temperature responses and an approximate 2-fold free spectral range (FSR) relationship. As the temperature rises, the interference spectrum of FPI1 gradually red-shifts, while the interference spectrum of FPI2 gradually blue-shifts, resulting in an enhanced HVE. Its temperature sensitivity is much higher than that of a single FPI, and the amplification rate is significantly higher than that of ordinary Vernier effect. Two enhanced HVE sensors S1 and S2 are developed using this method, but there is a certain difference in their FSR detuning. The experimental results reveal that within the temperature range of 30–35 °C, the temperature sensitivity of S1 and S2 reach − 44.39 nm/°C and − 23.14 nm/°C, respectively. Both S1 and S2 have extremely high temperature sensitivity, but FSR detuning has a significant impact on sensitivity amplification. Additionally, the proposed enhanced HVE sensor has good repeatability and stability in measuring temperature.